CREATING PUBLIC OPINION AND DEVELOPING SPATIAL CITIZENSHIP THROUGH MAPS: THE CASE OF ZARAGOZA, SPAIN - María ZÚÑIGA-ANTÓN; María SEBASTIÁN LÓPEZ; Rafael DE MIGUEL GONZÁLEZ; Ángel PUEYO CAMPOS (European Journal of Geography)
The current context of social transformation and urban changes increases the need for updated knowledge of living spaces. Citizens demand to have monitoring tools available applied to public actions affecting their local environment and neighbourhoods. Aware of this situation, geographers are in a position to provide these tools - urban thematic maps - to ensure citizen-geographical information interaction. The purpose of the present study was to investigate the efficacy of the GIS project Zaragoza map by map, in order to train, raise awareness, and empower citizens by using digital maps for their everyday urban space. Communicating by social networks involves generating public opinion trends on specific issues of daily life, such as transportation or public facilities, and thus, suggesting grassroots proposals for improving the built-up environment.